Radical interactionism and critiques of contemporary culture - Denzin, Norman K. (Studies in symbolic interaction ;, 2021)
This volume includes contributions from experts such as Gil Musolf, Michael Katovich, Joseph Kotarba, Norbert Wiley, Alina Pop, Marco Marzano, John Pruit, Amanda Pruit, Carol Rambo, Norman Conti, Laura Rosenberg, Krzysztof Konecki, Erick Laming, Christopher J. Schneider, Stacey Hannem, Robert Perinbanayagam, Veronica Manlow, and Christopher Ferree to provide a robust and interdisciplinary critique of contemporary culture. For its breadth and depth of research, this volume of Studies in Symbolic Interaction is essential reading for researchers and students across the social sciences interested in current symbolic interactionist thought and contemporary readings of social situations.